(untitled) (Sains Humanika, 2017)
This study took up a socio-phonetic investigation among Chinese learners of English by comparing English pronunciation produced by Chinese learners from two different countries: (1) Malaysia and (2) China. Two segmental sounds in English were chosen for comparison: (1) voiceless dental fricatives /Î¸/ and (2) alveolar liquids /r/; these sounds were known to be problematic for both groups of learners. The key motivation was to explore the extent to which these two groups of English learners behaved differently in terms of the selected sounds, given the differences in their nationalities, language exposure and social backgrounds. Production data were gathered from 10 Chinese learners each from Malaysia and China. They were all undergraduate students at Universiti Utara Malaysia. Two types of reading materials were used to elicit the data: (1) discreet items (i.e., an English wordlist each for /Î¸/ and /r/) and (2) connected speech (i.e., an English poem each for /Î¸/ and /r/). The data were auditorily analysed by three evaluators using a likert-scale evaluation form. The findings show that the Chinese learners from Malaysia were able to produce the /Î¸/ tokens more successfully as compared to those from China, particularly in the connected texts. Those who failed to produce the target sound substituted it with /t/ (for the learners from Malaysia) and /s/ or /z/ (for the learners from China). As for the /r/ tokens, it was found that both groups of learners could produce the target sound correctly across both reading materials; only a few of them substituted /r/ with /l/. The study highlights the importance of understanding the difficulties faced by specific groups of learners when mastering English pronunciation for different purposes. It also calls for further experimental research in language instructions that can effectively cater the needs of English language learners with diverse backgrounds.